On convergence of the accumulated insurance claim processes to the compound Poisson process - Banys, Rimas (Lietuvos matematikos rinkinys, 2005)
Convergence of the accumulated insurance claim processes is investigated when the number of clients of insurance company depeds on time. Conditions for convergence to the compound Poisson process in the function space D[0,∞) endowed with the Skorohod M1 and J1 topologies are obtained.
Keywords: functional limit theorems; compound Poisson process